Integration of chromosomal microarray analysis and whole-exome sequencing for prenatal diagnosis of fetuses with cardiac ultrasound anomalies - Wu, Youlan; Chen, Gui; Yang, Fang; Liu, Xiang; Qiang, Yawen; Wu, Renhua; Liu, Fang; Cheng, Weisheng; Yuan, Jing (Frontiers in Genetics, 2026)
BackgroundCongenital heart disease is among the most prevalent birth defects. This study aims to evaluate the clinical utility of chromosome microarray analysis (CMA) and whole-exome sequencing (WES) in prenatal diagnosis of genetic disorders in fetuses with cardiac ultrasound abnormalities.MethodsA retrospective cohort study analyzed 469 cases exhibiting fetal cardiac anomalies identified through prenatal ultrasound from November 2022 to July 2024. The study retrospectively assessed the patients' clinical features, observations, and pregnancy outcomes.ResultsOut of the 469 cases meeting the inclusion criteria, conventional karyotyping identified chromosomal aneuploidies in 17 cases (3.62%). CMA identified pathogenic or likely pathogenic findings, including both aneuploidies and copy number variants, in 35 cases, yielding a detection rate of 7.46% (95% CI: 5.24%–10.21%). The incremental yield of CMA over karyotyping was 3.84%. WES was performed on 59 CMA-negative/variants of undetermined clinical significance cases, identifying pathogenic/likely pathogenic variants in 6/59 (10.17%; 95% CI 3.82%–20.87%), providing a cohort-level incremental yield of 1.28% (6/469).ConclusionThis study highlights the clinical significance of CMA and WES in the prenatal diagnosis of genetic disorders in fetuses presenting with cardiac ultrasound abnormalities. It affirms the robust utility of CMA and WES methodologies in prenatal diagnosis and genetic counseling.